Comparative Study of the Impact of the Presence of Museums and Art Galleries on Cultural Tourism Activities in Bandung - Annisa Nur Majdina; Az-Zahra Dyah Zhafira Malik; Hasanah, Enny Lisdayanti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The evolution of visual trends and social media has transformed cultural spaces into tourist destinations that are not only educational but also aesthetic and interactive. In Bandung, conventional museums like the Geology Museum and the Indonesian Postal Museum focus on historical preservation and formal education, while contemporary art galleries like Selasar Sunaryo Art Space offer a dynamic, contextual, and participatory curatorial approach. This research compares the impact of museums and art galleries on cultural tourism, specifically in terms of visual appeal, content presentation strategies, digital adaptation, and their contribution to preserving local values. Using a descriptive-qualitative approach with a case study method, data was collected through literature reviews, field observations, and in-depth interviews with managers and visitors. The study found that Selasar Sunaryo, a non-profit art gallery managed by a foundation and led by curators, uses professional organizational practices with a mature structure, regular evaluations, and an active, measurable integration of digital technology and social media. In contrast, conventional museums face challenges in remaining relevant amid the expectations of the digital generation. These findings highlight the importance of a collaborative approach between museums and art galleries to strengthen their educational functions while increasing visual appeal. This collaboration can support an inclusive and sustainable urban cultural tourism ecosystem.